Understanding Grammars through Diachronic Change - Madariaga, Nerea (Frontiers in Psychology, 2017)
In this paper, I will vindicate the importance of syntactic change for the study of synchronic stages of natural languages, according to the following outline. First, I will analyze the relationship between the diachrony and synchrony of grammars, introducing some basic concepts: the notions of I-language/E-language, the role of Chomsky's (2005) three factors in language change, and some assumptions about language acquisition. I will briefly describe the different approaches to syntactic change adopted in generative accounts, as well as their assumptions and implications (Lightfoot, 1999, 2006; van Gelderen, 2004; Biberauer et al., 2010; Roberts, 2012). Finally, I will illustrate the convenience of introducing the diachronic dimension into the study of at least certain synchronic phenomena with the help of a practical example: variation in object case marking of several verbs in Modern Russian, namely, the verbs denoting avoidance and the verbs slušat'sja “obey” and dožidat'sja “expect,” which show two object case-marking patterns, genitive case in standard varieties and accusative case in colloquial varieties. To do so, I will review previous descriptive and/or functionalist accounts on this or equivalent phenomena (Jakobson, 1984 [1936]; Clancy, 2006; Nesset and Kuznetsova, 2015a,b). Then, I will present a formal—but just synchronic—account, applying Sigurðsson (2011) hypothesis on the expression of morphological case to this phenomenon. Finally, I will show that a formal account including the diachronic dimension is superior (i.e., more explanative) than purely synchronic accounts.